International Library of African Music (International Library of African Music, 1958)
With the end of 1958, the Library has now successfully completed its first experimental five year period. This was made possible through the generosity of various donors including the Nuffield Foundation, the Copper Mines of Northern Rhodesia, the Diamond Mines of Southern Africa, the Witwatersrand Native Labour Association, The Union Miniere du Haut Katanga, several Corporate Members including the Gold Mines of the Transvaal and Orange Free State, the South African Department of Arts and Science, Municipalities and other Industries and a number of Ordinary Members.
Keywords: African Music